Autophagy- and oxidative stress-related protein deregulation mediated by extracellular vesicles of human MJD/SCA3 iPSC-derived neuroepithelial stem cells and differentiated neural cultures - Liliana S. Mendonça; Ricardo Moreira; Daniel Henriques; Mónica Zuzarte; Teresa M. Ribeiro-Rodrigues; Henrique Girão; Luís Pereira de Almeida (Cell Death and Disease)
Abstract Extracellular vesicles (EVs) have been associated with the transport of molecules related to the pathological processes in neurodegenerative diseases. Machado-Joseph disease (MJD) is a neurodegenerative disorder triggered by mutant ataxin-3 protein that causes protein misfolding and aggregation resulting in neuronal death. To evaluate EVs’ role in the potential spread of disease-associated factors in MJD, in this study, EVs were isolated from human Control (CNT) and MJD induced-pluripotent stem cell-derived neuroepithelial stem cells (iPSC-derived NESC) and their differentiated neural cultures (cell cultures composed of neurons and glia). EVs were characterized and investigated for their ability to interfere with cell mechanisms known to be impaired in MJD. The presence of mRNA and proteins related to autophagy, cell survival, and oxidative stress pathways, and the mutant ataxin-3, was evaluated in the EVs. SOD1, p62, and Beclin-1 were found present both in CNT and MJD EVs. Lower levels of the p62 autophagy-related protein and higher levels of the oxidative stress-related SOD1 protein were found in MJD EVs. The oxidative stress-related CYCS mRNA and autophagy-related SQSTM1, BECN1, UBC, ATG12, and LC3B mRNAs were detected in EVs and no significant differences in their levels were observed between CNT and MJD EVs. The internalization of EVs by human CNT neurons was demonstrated, and no effect of the EVs administration was observed on cell viability. Moreover, the incubation of MJD EVs (isolated from NESC or differentiated neural cultures) with human CNT differentiated neural cells resulted in the reduction of SOD1 and autophagy-related proteins ATG3, ATG7, Beclin-1, LC3B, and p62 levels. Finally, a tendency for accumulation of ataxin-3-positive aggregates in CNT differentiated neural cells co-cultured with MJD differentiated neural cells was observed. Overall, our data indicate that EVs carry autophagy- and oxidative stress-related proteins and mRNAs and provide evidence of MJD EVs-mediated interference with autophagy and oxidative stress pathways.